Women as Guardians of Nature’s Fertility in the Legend of Dewi Sri: An Ecofeminist Study - Cahni Cahni; Ari Kusmiatun; Setyawan Pujiono (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aims to describe the representation of women, the representation of nature, and the relationship between women and nature in the legend of Dewi Sri based on an ecofeminist analysis. This study is motivated by the importance of literary studies that explore the relationship between women and the environment in the folklore of the Indonesian archipelago. The legend of Dewi Sri was chosen because it presents women as symbols of fertility and guardians of the survival of agrarian communities. This study employs a qualitative approach using a descriptive-analytical method. The data sources consist of the text of the Dewi Sri legend obtained through literature review. Data collection was conducted using the observe-and-record technique, while data analysis utilized an interactive analysis model encompassing data reduction, data presentation, and drawing conclusions. The results of the study indicate that women in the legend of Dewi Sri are represented as symbols of life, fertility, and protectors of agrarian communities. Nature is represented as a source of life, a spiritual space, and a symbol of community well-being. The relationship between women and nature in the legend of Dewi Sri demonstrates a harmonious connection built upon the values of fertility, protection, care, and the sustainability of life. The ecofeminist perspective in this legend demonstrates that women and nature are two interrelated elements crucial to maintaining the balance of life in the agrarian communities of the Nusantara. This study is expected to contribute to the development of ecofeminist studies in Indonesian oral literature, particularly in Nusantara folklore. Abstrak Penelitian ini bertujuan untuk mendeskripsikan representasi perempuan, representasi alam, serta relasi perempuan dan alam dalam legenda Dewi Sri berdasarkan kajian ekofeminisme. Penelitian ini dilatarbelakangi oleh pentingnya kajian sastra yang mengungkap hubungan antara perempuan dan lingkungan dalam folklor Nusantara. Legenda Dewi Sri dipilih karena menghadirkan perempuan sebagai simbol kesuburan dan penjaga keberlangsungan hidup masyarakat agraris. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif analitis. Sumber data penelitian berupa teks legenda Dewi Sri yang diperoleh melalui studi pustaka. Teknik pengumpulan data dilakukan dengan teknik simak dan catat, sedangkan teknik analisis data menggunakan model analisis interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perempuan dalam legenda Dewi Sri direpresentasikan sebagai simbol kehidupan, kesuburan, dan pelindung masyarakat agraris. Alam direpresentasikan sebagai sumber kehidupan, ruang spiritual, dan simbol kesejahteraan masyarakat. Relasi perempuan dan alam dalam legenda Dewi Sri menunjukkan hubungan harmonis yang dibangun melalui nilai kesuburan, perlindungan, kepedulian, dan keberlanjutan hidup. Perspektif ekofeminisme dalam legenda ini memperlihatkan bahwa perempuan dan alam merupakan dua unsur penting yang saling berkaitan dalam menjaga keseimbangan kehidupan masyarakat agraris Nusantara. Penelitian ini diharapkan dapat memberikan kontribusi terhadap pengembangan kajian ekofeminisme dalam sastra lisan Indonesia, khususnya pada folklor Nusantara.